The flounder - Grass, Gèunter 1927-2015 (London Secher & Warbury, 1978)
Based loosely on Grimm's The Fisherman and his Wife, this triumphant blend of folk tale and contemporary story takes place over the course of nine months, during which the wife of the narrator becomes pregnant and is regaled with tales of the various cooks the fisherman has met throughout his life. The emerging themes of the novel expose the periods when men made history and women's contributions went largely, in some cases gravely, unrecognized. Inventive, imaginitive and irreverent, this humorous, fundamentally brilliant novel highlights the value of modern-day myth and timeless legend.
First month: Third breast -- What I write about -- Nine and more cooks -- Awa -- How the flounder was caught -- Division of labor -- How the flounder was caught a second time -- Dreaming ahead -- How the flounder was prosecuted by the Ilsebills -- Meat -- Where the stolen fire was briefly hidden -- What we lack -- Hospitably from horde to horde -- Dr. Affectionate -- Fed -- Wurzel mother -- Demeter -- What a cast-iron spoon is good for -- How I see myself -- Oh, Ilsebill -- At the end -- What I don't want to remember -- Second month : How we became city dwellers -- Quarrel -- Dishwashing -- Elaine Migraine -- Libber, libber -- Like my Dorothea -- Like at the movies -- Scania herring -- To Ilsebill -- My dear Dr. Stachnik -- Surplus value -- Third month: How the flounder was protected against aggresion -- When I was her kitchen boy -- Vasco returns -- Three questions -- Too much -- Esau says -- Last meal -- Tarred and feathered -- Fat Gret's ass -- Delay -- Flounder's ideas about nunnish life -- Hasenpfeffer -- Whoever wants to cook in her footsteps -- Cook kisses -- Fourth month: Inspection of feces -- Empty and alone -- Burden of an evil day -- Turnips and Ganseklein -- Why the flounder tried to rekindle two cold stoves -- Late -- Fishily on love and poetry -- Agnes remembered over boiled fish -- It seems his name was Axel -- Excrement rhymed -- Only one was burned as a witch -- Immortal -- Fifth month: What potato flour is good for (and against) -- Told while pounding acorns, plucking geese, peeling potatoes -- Plaint and prayer of the farm cook Amanda Woyke -- Ole Fritz -- Speaking of the weather -- How letters were quoted in court -- Why potato soup tastes heavenly -- Starvation -- Great leap forward and the Chinese world food solution -- Boiled beef and historical millet -- Both -- Sixth month: Dresses from India -- Sophie -- Other truth -- Beyond the mountains -- Gathering mushrooms -- Hidden under sorrel -- Afraid -- Three at table -- Nothing but daughters -- Continuous generation -- Seventh month: With Ilsebill, too -- Lena dishes out soup -- Simple woman -- All -- Nail and rope -- Home-fried potatoes -- Bebel's visit -- Trip to Zurich -- Where she left her specs -- Obituary for Lena -- Eighth month: Father's day -- Ninth month: Lud -- Late -- Why she vomited -- Vestimentary preoccupations, feminine proportions, last visions -- Womenal -- On Mon -- Conversation -- What we wish for -- Man oh man -- Three meals of pork and cabbage.
Translation of Der Butt.
Keywords: German fiction -- 20th century -- Translations into English; Cooks -- Fiction; Fishes -- Fiction